(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background and Objectives: Endoscopic laser dacryocystorhinostomy(DCR) is now a well established, effective approach to relieve nasolacrimal duct obstruction.The aim of DCR surgery is to create a permanent opening between the lacrimal sac & nasal mucosa in patient of chronic dacryocistitis. There are many methods to perform DCR but our approach was diode laser assisted endoscopic DCR. The Objective is to study the outcomes of diode laser assisted endoscopic DCR. Material and Methods: This hospital based prospective non-randomized interventional clinical trial included 49 patients with chronic dacryocystitisat National Institute of ENTbetween august 2015 to July 2016. Success and complications were assessed by evaluating the patient at 1 week, 1 month, 3 month,6 month postoperatively and at least 3 month after removal of silicon tube those who were intubated by nasal endoscopy and sac patency test. Success was defined as absence of epiphora and patency of lacrimal drainage system. Results: Mean age with SD was 44.96 ±15.807 (Range 13 – 70 years). Patients between age group 40 – 60 yrs. was the highest (40.8%), Female were predominant 35 (71.4%) than male. Male Female Ratio was 1: 2.5. Septoplasty for DNS in 8 (16.33%) cases, turbinoplastyfor hypertrophied terbinatein 1 case were performed. Complications were injury to middle turbinate, sump syndrome, syneachia and granulation tissue formation. Overall success rate of DCR was seen in 87.76% cases. Conclusion: Laserassisted endoscopic DCR surgery eliminate the need of conventional external DCR. It is easy to perform, cosmetically good, high tech and has excellent outcome. Bangladesh J Otorhinolaryngol; April 2018; 24(1): 79-84